2019
DOI: 10.1021/acsaem.9b01370
|View full text |Cite
|
Sign up to set email alerts
|

High Voc upon KF Post-Deposition Treatment for Ultrathin Single-Stage Coevaporated Cu(In, Ga)Se2 Solar Cells

Abstract: A simplified Cu(In, Ga)Se2 (CIGS) solar cell structure based on a 500 nm thin CIGS layer is presented. The absorber layers are grown with a single-stage co-evaporation process and various KF post deposition treatments (KF-PDT) are performed. The KF-PDT leads to an efficiency increase from 7% to 12%. For all cells an increase in open circuit voltage (Voc) and fill factor is measured, which is attributed to an improved pn junction. By changing the annealing conditions an additional Voc increase is measured. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 54 publications
0
32
0
Order By: Relevance
“…There were no major differences in J0 found between the covered and the exposed samples, though the Voc of the covered sample is significantly higher. A more detailed study on the effect of covering of the absorber layer during the post anneal can be found elsewhere [10]. We showed in a previous contribution that the apparent acceptor concentration NA increases after KF treatment.…”
Section: A Solar Cellsmentioning
confidence: 69%
“…There were no major differences in J0 found between the covered and the exposed samples, though the Voc of the covered sample is significantly higher. A more detailed study on the effect of covering of the absorber layer during the post anneal can be found elsewhere [10]. We showed in a previous contribution that the apparent acceptor concentration NA increases after KF treatment.…”
Section: A Solar Cellsmentioning
confidence: 69%
“…The shutter is opened again when the elemental fluxes are stable. This will result in a rather flat gallium profile, similar to the single stage process [19], although there was still a copper rich stage during the growth. The substrate temperature was set at 550 • C for all the stages.…”
Section: Methodsmentioning
confidence: 89%
“…When the surface recombination decreases following chemical surface passivation, the open circuit voltage ( V oc ) and FF are expected to improve. [ 31 ] An increase in V oc can be estimated from the PL yield, by transforming the Lasher–Stren–Wurfel equation into [ 32 ] ΔμASref=kTln(IASIref)…”
Section: Resultsmentioning
confidence: 99%
“…Thanks to this process a flat and homogenous Ga profile was achieved in the CIGS layer. [ 32 ] Three sets with different CGI ratios were created. The sets were named according to the CGI ratio; CGI was 0.72 for the Cu‐poor sample, 0.8 for the Cu‐desired sample, and 0.92 for the Cu‐rich sample.…”
Section: Methodsmentioning
confidence: 99%